Exact k-Component Graph Learning for Image Clustering. (6th August 2020) - Min, Yufang; Zhang, Yaonan
Abstract : The performance of graph-based clustering methods highly depends on the quality of the data affinity graph as a good affinity graph can approximate well the pairwise similarity between data samples. To a large extent, existing graph-based clustering methods construct the affinity graph based on a fixed distance metric, which is often not an accurate representation of the underlying data structure. Also, they require postprocessing on the affinity graph to obtain clustering results. Thus, the results are sensitive to the particular graph construction methods. To address these two drawbacks, we propose a k -component graph clustering (k -GC) approach to learn an intrinsic affinity graph and to obtain clustering results simultaneously. Specifically, k -GC learns the data affinity graph by assigning the adaptive and optimal neighbors for each data point based on the local distances. Efficient iterative updating algorithms are derived for k -GC, along with proofs of convergence. Experiments on several benchmark datasets have demonstrated the effectiveness of k -GC.